Thermoelectric properties of In1Co4Sb12+δ: role of in situ formed InSb precipitates, Sb overstoichiometry, and processing conditions. Issue 5 (17th January 2023) - Ivanova, Alexandra; Novitskii, Andrei; Serhiienko, Illia; Guélou, Gabin; Sviridova, Tatyana; Novikov, Sergey; Gorshenkov, Mikhail; Bogach, Aleksei; Korotitskiy, Andrey; Voronin, Andrei; Burkov, Alexander; Mori, Takao; et al.
Abstract : The demonstration of strong coupling between the processing conditions, microstructure, distribution, shape, and size of InSb precipitates in In-filled Co4 Sb12 . Abstract : In-filled skutterudites In x Co4 Sb12 have attracted much attention due to their relatively high thermoelectric performance, which, in turn, is attributed to the In atoms acting as rattlers in the skutterudite voids and to the formation of InSb precipitates when the In solubility limit is exceeded (0.22 ≤ x max ≤ 0.27). In this work, to suppress the formation of the unwanted CoSb2 phase and favor the formation of InSb precipitates, the following composition of In1 Co4 Sb12+ δ with In concentration much higher than the solubility limit and Sb overstoichiometry was used. Three sets of bulk specimens with a nominal composition of In1 Co4 Sb12+ δ were synthesized by conventional induction melting followed by (1) ball milling (BM) and spark plasma sintering (SPS), (2) BM and SPS followed by high-temperature annealing, and (3) melt spinning and SPS. The utilization of different sample preparation methods and processing conditions leads to samples with different microstructures and InSb precipitates of different shapes, sizes, and distributions. Thus, for all samples with the same nominal composition of In1 Co4 Sb12+ δ, zT max varies from 0.7 to 1.3 at 673 K only because of microstructural modification. A maximum zT value of around 1.3 was obtained at 673 K for the sample prepared using induction melting followed by annealing, melt spinning, and SPS.